Fundamental Spectral Theory of Fractional Singular Sturm-Liouville Operator - Bas, Erdal (Hindawi Ltd, 2013)
We give the theory of spectral properties for eigenvalues and eigenfunctions of Bessel type of fractional singular Sturm-Liouville problem. We show that the eigenvalues and eigenfunctions of the problem are real and orthogonal, respectively. Furthermore, we prove new approximations about the topic.